Rapid wet chemical synthesis for 33P-labelled hydroxyapatite – An approach for environmental research. (October 2018) - Wolff, J.; Hofmann, D.; Amelung, W.; Lewandowski, H.; Kaiser, K.; Bol, R.
Abstract: Apatite is the principal primary phosphorus (P) source in the environment; yet there is no consensus on how it can be synthesized for controlled microcosm studies, particularly not in labelled form. Here, we present a methodology that allows for the production of stoichiometric 33 Phosphorus ( 33 P)-labelled hydroxyapatite powders produced by a simple and fast wet chemical procedure, with different precursor compounds and at different reaction (25, 40, 60 and 80 °C) and calcination (100 and 200 °C) temperatures. The resulting morphological structures were analysed by Raman spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The results showed that rapid synthesis of hydroxyapatite is successful using 33 P-labelled di-ammonium hydrogen phosphate and calcium nitrate with a Ca/P ratio of 1.67 in less than 30 h. Crystallinity increased with increasing reaction temperatures. Solubility tests confirmed a strong pH dependency for all hydroxyapatites at pH values <3.7. To our knowledge this is the first procedure that can rapidly synthesize radioactive labelled and chemically pure hydroxyapatite of different crystallinities: It can be easily modified to allow for labelling with other isotopes, such as 44 Ca or 18 O, in order to provide hydroxyapatite in reproducible manner for investigating the availability and uptake of P from apatite in future soil and environmental studies and beyond. Highlights: First chemical synthesis to produce 33 P-labelled hydroxyapatites. Synthesizing powders with various degrees of crystallinity in less than 30 h. Hydroxyapatites of varying crystallinity, and thus, solubility were produced. Near-natural hydroxyapatites suitable for tracer-based environmental research.